A new perspective on apoptosis: Its impact on meat and organoleptic quality in different animals - Boin Lee; Young Min Choi (Food Chemistry: X)
Apoptosis serves as the initial phase in the conversion of muscle to meat, driving key biochemical and morphological changes in the postmortem muscle. To effectively improve and control meat quality across different animal species, it is important to gather more information on the mechanisms by which apoptotic potential, mediated through the interaction of apoptosis-related molecules, influences meat quality variations. The apoptotic potential, determined by the balance between apoptotic and anti-apoptotic molecules, such as Ca2+, cytochrome c, caspases, and heat shock proteins, varies among different species. A moderate to rapid apoptotic rate can improve textural properties in species with a higher proportion of type I fibers, such as cattle. In contrast, in species with a predominance of type IIB fibers, such as pork and poultry, rapid apoptosis can lead to undesirable quality traits. Therefore, understanding these species-specific apoptotic responses is critical for improving and maintaining meat quality across various species.